Updated survey of the steroid-converting enzymes in human adipose tissues. Issue 147 (March 2015) - Tchernof, André; Mansour, Mohamed Fouad; Pelletier, Mélissa; Boulet, Marie-Michèle; Nadeau, Mélanie; Luu-The, Van
Highlights: We provide a survey of the many steroid-converting enzymes found in adipose tissues. Their activities and potential roles are also reviewed. Some enzymes may bear relevance for adipose tissue physiology and obesity. Studies are needed on adipose steroid conversions and obesity, diabetes or cancer. Abstract: Over the past decade, adipose tissues have been increasingly known for their endocrine properties, that is, their ability to secrete a number of adipocytokines that may exert local and/or systemic effects. In addition, adipose tissues have long been recognized as significant sites for steroid hormone transformation and action. We hereby provide an updated survey of the many steroid-converting enzymes that may be detected in human adipose tissues, their activities and potential roles. In addition to the now well-established role of aromatase and 11β-hydroxysteroid dehydrogenase (HSD) type 1, many enzymes have been reported in adipocyte cell lines, isolated mature cells and/or preadipocytes. These include 11β-HSD type 2, 17β-HSDs, 3β-HSD, 5α-reductases, sulfatases and glucuronosyltransferases. Some of these enzymes are postulated to bear relevance for adipose tissue physiology and perhaps for the pathophysiology of obesity. This elaborate set of steroid-converting enzymes in the cell types of adipose tissue deserves further scientific attention. Our work on 20α-HSD (AKR1C1), 3α-HSD type 3 (AKR1C2) and 17β-HSD type 5 (AKR1C3) allowed us to clarify the relevance of these enzymes for some aspects of adipose tissue function. For example, down-regulation of AKR1C2 expression in preadipocytes seems to potentiate the inhibitory action of dihydrotestosterone on adipogenesis in this model. Many additional studies are warranted to assess the impact of intra-adipose steroid hormone conversions on adipose tissue functions and chronic conditions such as obesity, diabetes and cancer.